Effect of canopy and nutrient management on senile orchards of Indian gooseberry (Emblica officinalis) cv Francis - TIWARI, DIVYA; SINGH, H K; SHUKLA, A K (The Indian Journal of Agricultural Sciences, 2015)
A study was conducted on 15 years old senile orchard of Indian gooseberry (Emblica officinalis G.) cv Francis to convert into productive through canopy and nutrient management. The results revealed that 50% pruning of previous season growth (P2) was statistically superior which resulted in maximum duration of flowering, fruit set and retention, yield, physical and chemical qualities of fruit and leaf as well as soil nutrient status. Further, nutrient management revealed that application of 40 kg FYM (M1) resulted maximum fruit set, retention, yield and phosphorus content in leaves and NPK in soil and minimum fruit drop, days taken to maturity and fibre content. Similarly 100 per cent RDF (N2) resulted in maximum fruit set (64.90 %), retention (20.51 %), yield (118 kg/tree), nitrogen and phosphorus content in leaves (2.46 and 0.44 %) as well as in soil (238.6 and 17.75 kg/ha). A critical observation of the results showed that interactions had been most effective to improve yield and quality parameters of fruits and nutrient status in leaves of aonla as well as soil than the individual application of different levels of pruning, organic manure and nutrient. Among flowering, fruiting and yield parameters, maximum duration of flowering (29 days), fruit set (74.61 %), retention (28.33 %) and yield (145 kg/tree) and minimum fruit drop (71.67 %) and days taken to fruit maturity (216 days) was found under P2M2N2 followed by P2M2N1. Interaction P2M2N2 has been noticed statistically superior to enhance physical and chemical characteristics of fruit followed by P2M2N1. This treatment has not only enhanced bearing and quality parameters in aonla but also increased the leaf nutrient status as well as soil fertility status. A significant increased yield of Indian gooseberry with application of pruning intensity, organic and inorganic nutrients was found due to vigorous vegetative growth and increased chlorophyll content, which together accelerated the photosynthesis that increased the supply of carbohydrates to plants. There is a positive correlation among nutrient doses with leaf nutrient content yield and quality of fruits. The supplemented organic manures have improved the physical, chemical and biological activities of soil which helped in better nutrient absorption by plants, resulting higher yield.